1996
DOI: 10.1107/s0108768196000481
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ce2Pt6Ga15: interplanar disorder from the Ce2Ga3 layers

Abstract: The structure of the heavy fermion compound CezPt6Gal5 has been determined from neutron powder and X-ray/neutron single-crystal diffraction. Examination of symmetry equivalence among the single-crystal data, as well as the good fit of the powder data to the final structural arrangement, with all the atoms on symmetry sites, suggests that the correct space group is P63/mmc. The structure is unusual in that Ce layers have 1/3 of the Ce atoms replaced by groups of three Ga atoms; distances between atoms in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 2 publications
(5 reference statements)
2
26
0
Order By: Relevance
“…The lattice parameters of the RE 2 Pt 6 X 15 ( X = Al, Ga) series were refined from Guinier powder patterns using the hexagonal subcell of the RE 0.67 Pt 2 Al 5 series along with space group P 6 3 / mmc . The lattice parameters, including the ones from the literature, are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lattice parameters of the RE 2 Pt 6 X 15 ( X = Al, Ga) series were refined from Guinier powder patterns using the hexagonal subcell of the RE 0.67 Pt 2 Al 5 series along with space group P 6 3 / mmc . The lattice parameters, including the ones from the literature, are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…For Gd 0.67 Pt 2 Al 5 (≡ Gd 2 Pt 6 Al 15 ), antiferromagnetic ordering at a Néel temperature of T N = 7.5 K and 8 K was reported, single crystals of Yb 2 Pt 6 Al 15 were found to exhibit a broad maximum at low temperatures, in line with a Kondo lattice system with a large degeneracy of the local moments . For the heavier homologue Ga, also some compounds with the RE 0.67 Pt 2 Ga 5 / RE 2 Pt 6 Ga 15 composition ( RE = La, Ce, Pr, Nd, Sm, Gd, Er,) have been reported to crystallize in the Sc 0.6 Fe 2 Si 4.9 type structure. Of these, Ce 2 Pt 6 Ga 15 was characterized to be a heavy fermion material , .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The resultant crystals are in the form of hexagonal prisms, reflecting thier intrinsic crystal structure with typical dimensions of 4 × 4 × 10 mm. The crystallographic characterization is performed by means of the x-ray powder diffraction on crushed pieces of obtained single crystals [5]. No traces of impurity phases are detected.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that Ce 2 Pt 6 Ga 15 crystallizes in the hexagonal Ce 4 Pt 12 Ga 30 -type structure with the space group P6 3 /mmc [5]. This structure has an intrinsic two dimensional character with a large ratio c/a ∼ 4.…”
Section: Introductionmentioning
confidence: 99%